2022
DOI: 10.1038/s41417-022-00504-y
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-21 guide and passenger strand regulation of adenylosuccinate lyase-mediated purine metabolism promotes transition to an EGFR-TKI-tolerant persister state

Abstract: In EGFR-mutant lung cancer, drug-tolerant persister cells (DTPCs) show prolonged survival when receiving EGFR tyrosine kinase inhibitor (TKI) treatments. They are a likely source of drug resistance, but little is known about how these cells tolerate drugs. Ribonucleic acids (RNAs) molecules control cell growth and stress responses. Nucleic acid metabolism provides metabolites, such as purines, supporting RNA synthesis and downstream functions. Recently, noncoding RNAs (ncRNAs), such as microRNAs (miRNAs), have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…These data might provide clues to recent discoveries that AICAR's anticancer roles are independent of AMPK, indicating that AICAR plays a prominent role in binding to other targets [18,19]. Targeting lung cancer cells with AICAR in vitro and in vivo has demonstrated that AICAR is an effective anticancer molecule by our and other labs [20,21]. It is still not well known how AICAR targets these lung cancer cells.…”
Section: Introductionmentioning
confidence: 64%
“…These data might provide clues to recent discoveries that AICAR's anticancer roles are independent of AMPK, indicating that AICAR plays a prominent role in binding to other targets [18,19]. Targeting lung cancer cells with AICAR in vitro and in vivo has demonstrated that AICAR is an effective anticancer molecule by our and other labs [20,21]. It is still not well known how AICAR targets these lung cancer cells.…”
Section: Introductionmentioning
confidence: 64%
“…RNA extraction was performed using mirVana miRNA Isolation Kit (Cat#AM1560, Invitrogen) as described previously 79 . A total of 500 ng RNA each sample was input for the Reverse Transcription reaction to acquire the cDNA.…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
“…In addition, ectopic overexpression of miR-506-3p in erlotinibresistant cells targeted Sonic Hedgehog (SHH), increased E-cadherin expression, inhibited vimentin expression, and reversed EMT to a mesenchymal phenotype epithelial-like transformation, thereby counteracting EMT-mediated chemoresistance, increasing sensitivity to apoptosis, decreasing cell stemness, reducing proliferation, and enhancing sensitivity to erlotinib [118] (Figure 5). Numerous studies have shown that multiple miRNAs are extensively involved in EGFR-TKI regulation, suggesting that miRNAs may be new therapeutic molecules and biomarkers for anti-EGFR therapy and have a positive role in reversing drug resistance and improving sensitivity [119][120][121]. Alessandro et al collected plasma samples from 39 patients with advanced EGFR-mutated NSCLC treated with EGFR-TKIs, assessed the expression levels of miRNAs and found that miR-21 could be a useful indicator to monitor the effect of EGFR-TKI treatment [122].…”
Section: Mirna-assisted Targeted Therapymentioning
confidence: 99%
“…Alessandro et al collected plasma samples from 39 patients with advanced EGFR-mutated NSCLC treated with EGFR-TKIs, assessed the expression levels of miRNAs and found that miR-21 could be a useful indicator to monitor the effect of EGFR-TKI treatment [122]. In addition, Zhang et al identified miR-608 and miR-4513 single nucleotide polymorphisms as independent candidate biomarkers for pre- Numerous studies have shown that multiple miRNAs are extensively involved in EGFR-TKI regulation, suggesting that miRNAs may be new therapeutic molecules and biomarkers for anti-EGFR therapy and have a positive role in reversing drug resistance and improving sensitivity [119][120][121]. Alessandro et al collected plasma samples from 39 patients with advanced EGFR-mutated NSCLC treated with EGFR-TKIs, assessed the expression levels of miRNAs and found that miR-21 could be a useful indicator to monitor the effect of EGFR-TKI treatment [122].…”
Section: Mirna-assisted Targeted Therapymentioning
confidence: 99%